2016
DOI: 10.5812/atr.30011
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Bicycle Safety Helmets in Preventing Facial Injuries in Road Accidents

Abstract: BackgroundThe effectiveness of bicycle safety helmets in preventing head injuries is well- documented. Recent studies differ regarding the effectiveness of bicycle helmets in preventing facial injuries, especially those of the mid-face and the mandible.ObjectivesThe present study was conducted to determine the protective effect of a bicycle helmet in preventing mid-face and mandibular fractures.Patients and MethodsData from an accident research unit were analyzed to collect technical collision details (relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 35 publications
0
25
1
Order By: Relevance
“…[38][39][40] Some authors emphasized that wearing bicycle helmets did not reduce the incidence of mid-facial fractures and was even associated with an increased risk of mandibular fractures. 37 Contrary to the abovementioned articles, in our studies, the most common injuries were those of the upper extremities (48.53% of all injuries) and lower extremities (32.38%). Injuries of the upper extremities, including wounds, were more often observed in the male group.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…[38][39][40] Some authors emphasized that wearing bicycle helmets did not reduce the incidence of mid-facial fractures and was even associated with an increased risk of mandibular fractures. 37 Contrary to the abovementioned articles, in our studies, the most common injuries were those of the upper extremities (48.53% of all injuries) and lower extremities (32.38%). Injuries of the upper extremities, including wounds, were more often observed in the male group.…”
Section: Discussioncontrasting
confidence: 85%
“…35 Cyclists are also at a higher risk of undergoing facial fractures. 37 The studies on the impact of wearing helmets on injuries of the facial region led to controversial conclusions. [38][39][40] Some authors emphasized that wearing bicycle helmets did not reduce the incidence of mid-facial fractures and was even associated with an increased risk of mandibular fractures.…”
Section: Discussionmentioning
confidence: 99%
“…19 Stier et al observed that the most commonly occurring fractures were those that concerned the nasal bone, orbital bone, zygomatic bone, maxilla and mandible. 20 Some authors also confirmed that falling is one of the major causes of injury, especially among older people. 1,21 However, most researchers regarded collisions as the main causes of accidents.…”
Section: Discussionmentioning
confidence: 84%
“…It should also be emphasized that the increased accident rate of the transport mode is affected by a number of often diverse factors, including: poor infrastructure, difficult weather conditions, ignorance or intentional violation of traffic rules, incorrect marking (lack of lighting, reflective elements) ), using electronic devices while driving (music players, mobile phones, navigation, training counters). In addition, the data presented in the literature on the subject shows that car drivers are most of the collisions that are not aware of the presence of cyclists traveling alongside or behind them [1], [4], [10], [16], [20].…”
Section: Introductionmentioning
confidence: 99%